Characterization of DCL4 missense alleles provides insights into its ability to process distinct classes of dsRNA substrates. (23rd May 2018) - Montavon, Thomas; Kwon, Yerim; Zimmermann, Aude; Hammann, Philippe; Vincent, Timothée; Cognat, Valérie; Bergdoll, Marc; Michel, Fabrice; Dunoyer, Patrice
Summary: In the model plant Arabidopsis thaliana, four Dicer‐like proteins (DCL1–4) mediate the production of various classes of small RNAs (sRNAs). Among these four proteins, DCL4 is by far the most versatile RNaseIII‐like enzyme, and previously identified dcl4 missense alleles were shown to uncouple the production of the various classes of DCL4‐dependent sRNAs. Yet little is known about the molecular mechanism behind this uncoupling. Here, by studying the subcellular localization, interactome and binding to the sRNA precursors of three distinct dcl4 missense alleles, we simultaneously highlight the absolute requirement of a specific residue in the helicase domain for the efficient production of all DCL4‐dependent sRNAs, and identify, within the PAZ domain, an important determinant of DCL4 versatility that is mandatory for the efficient processing of intramolecular fold‐back double‐stranded RNA (dsRNA) precursors, but that is dispensable for the production of small interfering RNAs (siRNAs) from RDR‐dependent dsRNA susbtrates. This study not only provides insights into the DCL4 mode of action, but also delineates interesting tools to further study the complexity of RNA silencing pathways in plants, and possibly other organisms. Significance Statement: DCL4 is the most versatile RNaseIII‐like enzyme in plants. An in‐depth study of DCL4 missense alleles pinpoints key residues in its helicase and PAZ domain that are specifically required in DCL4 cleavage efficiency and versatility.